(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
[...] When our young architects, taken by the hand of your young archaeologists, will learn the equal value of every wall, every stone, every space that can be understood in the avaricious remains that archeology makes available in the patient work of reconstitution of the reality of ancient cities, behold, they will have learned a new way of observing the current city as well, of understanding its reality and with it the reality of their future work. They will have learned to look at the modern city and their work with the eyes of an archaeologist.